2008
DOI: 10.1111/j.1745-7599.2008.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in nurses, advanced practice nurses, and nurse educators

Abstract: Purpose: To quantify the incidence of overweight and obesity in nursing professionals and assess nurses' knowledge of obesity and associated health risks.Data sources: A mailed survey to 4980 randomly selected registered nurses from one state in each of six geographic regions. Response rate was 15.5% (n = 760). Descriptive statistics were calculated for continuous variables; categorical variables were summarized with frequency counts.Results: The grand mean body mass index (BMI) of nurses surveyed was 27.2. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
136
3
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 5 publications
9
136
3
8
Order By: Relevance
“…Be that as it may, it seems that physicians themselves are incognizant of their effectiveness in assisting patients in CVD prevention, which makes it vitally important that educational interventions be devised for physicians with a view to improving the quality of preventive care in connection with CVD (44,45). Nurses, another significant component of health care teams, can make major contributions to CVD prevention (44,45), but their endeavors to effect necessary modifications in the society's lifestyle are hampered by formidable obstacles (46). It seems that quantitative and qualitative research is needed to analyze the roles and responsibilities of health care professionals and determine the reasons for their unwillingness to control CVD risk factors (47).…”
Section: Discussionmentioning
confidence: 99%
“…Be that as it may, it seems that physicians themselves are incognizant of their effectiveness in assisting patients in CVD prevention, which makes it vitally important that educational interventions be devised for physicians with a view to improving the quality of preventive care in connection with CVD (44,45). Nurses, another significant component of health care teams, can make major contributions to CVD prevention (44,45), but their endeavors to effect necessary modifications in the society's lifestyle are hampered by formidable obstacles (46). It seems that quantitative and qualitative research is needed to analyze the roles and responsibilities of health care professionals and determine the reasons for their unwillingness to control CVD risk factors (47).…”
Section: Discussionmentioning
confidence: 99%
“…However many, 53% lacked the initiative to make lifestyle changes to intervene in their own OW/OB disease processes. As many as 76% of the practitioners do not address the issue upon client encounter with those who meet the diagnostic criteria for overweight or obese states, although 93% recognize overweight and obesity as a disease that requires some intervention [7].…”
Section: Findings Of Several Studies Of Nurses One In the United Stamentioning
confidence: 99%
“…Too often nurses exert a tremendous deal of energy and passion into caring for patients, students and their families. Nurses must make their own health and welfare a priority as well [7].…”
mentioning
confidence: 99%
“…Evidence suggests that HCPs are gaining weight like the general population [1][2][3]. A study from the US showed that 40% of the paediatricians were overweight or obese [4] whereas a study conducted among Mexican physicians reported a higher (74%) proportion of physicians as either overweight or obese [5].…”
mentioning
confidence: 99%
“…Studies from the US [2], Canada [8], European Unions' countries [9], Egypt [10,11], Saudi Arabia [12], Iran [13], Malaysia [14] and Pakistan [15] have reported a growing burden of obesity among trainee HCPs. Similarly, data from the Behavioural Risk Factor Surveillance System (BRFSS) which is the world's largest, on-going telephone health survey system conducted by the Centre for Disease Control and Prevention (CDC) and has a representative sample of the US population has revealed that healthcare workers (HCWs) may not always be able to model healthy behaviours for their patients [16].…”
mentioning
confidence: 99%